Prototype of a Digital Measuring Device Based on Atmega 328P for Measuring Current, Voltage, Electrical Power, and RLC Components - Putri, Risa Amelia; Supriyanto, Amir; Surtono, Arif (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Research on digital measuring device prototypes has developed over the past few years. However, there are still challenges in measuring current, voltage, electrical power, and RLC component parameters accurately. This research aims to design a digital system to measure electrical quantities such as current, voltage, resistance, inductance, and capacitance using Atmega 328P. Data retrieval is done by implementing the system as a whole, namely the AC and DC electrical measurement system and the measurement of RLC components. The results showed that the system can measure and display the result of measuring current, voltage, electric power, and RLC components correctly. The accuracy percentage for the components measuring instrument on the resistor test is 99.35%, the error is 0.65%, and the precision is 99.87%. In the inductor test measurement, the percentage value of accuracy is 94.11%, the error is 5.89%, and the precision is 96.77%. In the capacitor test measurement, the accuracy percentage is 98.03%, the error is 1.97%, and the precision is 98.65%. On the DC voltage sensor, the accuracy percentage is 97.31%, error 2.69%, and precision 99.77%.